Plan de negocio para la creación de una mcroempresa dedicada a la producción y comercialización de productos de limpieza ecológicos biodegradables, Cantón La Maná. Quevedo. 2015 - Gallo Matute, Paúl Ignacio (2015)
This research project was conducted with the aim of presenting a business model applying the knowledge acquired during the career of business management through the theme: "Business Plan for the creation of a Micro-enterprise dedicated to the production and marketing of products biodegradable organic cleaning, Cantón La Maná, 2015 ". The methods used in this research were: deductive, inductive statistical and analytical method; the type of applied research was field research since it had to be in direct contact with the target market through the use of surveys to 382 women La Maná City aged between 15 and 59 years old. When the business plan has obtained the result that the products of cleaning are used by 100% of respondents, 67% of the population showed little loyalty with existing products establishing such percentage as unmet demand, so that products of Ecological Cleaning Biodegrables proved accepted 100% of the market so dissatisfied implantation Microenterprise is quite promising. It should be noted that this project has established requirements for inputs and equipment, organization and legislation needed to implement Microenterprise, same to be established in the form of limited company with a number of collaborators formed by two workers and person in charge of sales and administration, just as it would have the external advice of an accountant. This project is beneficial for your investment because you took an TIR of 55% and VAN of $ 47.554,60 after 5 years of life before planned an initial investment of $ 43.953,00 from two equity partners in 50% contribution respectively.